Increased-Resolution OCT Thickness Mapping of the Human Macula: A Statistically Based Registration - Bernardes, Rui (2008)
To describe the development of a technique that enhances spatial resolution of retinal thickness maps of the Stratus OCT (Carl Zeiss Meditec, Inc., Dublin, CA). A retinal thickness atlas (RT-atlas) template was calculated, and a macular coordinate system was established, to pursue this objective.